A Peer-Assessment Based Approach for Teaching Microprogramming - Kanika; Chakraverty, Shampa; Chakraborty, Pinaki (Journal of Engineering Education Transformations, 2021)
The course on microprocessors introduces undergraduate computer science students to hardware-level programming. The course was taught by the authors to 130 students in context of the 8085 and 8086 microprocessors in the Spring semester of 2019. The students executed their programs on hardware kits, and participated in a double-blind peerassessment exercise in which they assessed and rated programs written by their peers and also advised them on improving the efficiency and readability of their programs. It was found that the peer-assessment exercise helped the students to learn better and score 6.97% higher marks in examination (Z=2.68, P&#;60;0.05). There was a moderately strong correlation (r=0.43, P&#;60;0.05) between the ratings received by the students from their peers and their score in the postintervention test. The students felt that they benefitted from the advice they received from their peers and 78% of the students agreed with the ratings they received. The students felt that assessing programs written by others also helped them in improving their own programming skills.